Analisis Keuntungan Dan Nilai Tambah Agroindustri Pengolahan Ikan Asin Labuhan Maringgai - Maulana Nafiul Anwar, Angga; Abidin, Zainal; Murniati, Ktut (Journal of Food System & Agribusiness, 2024)
As an area with the highest total production catch in Lampung with a total value of 42,000 tons per year, East Lampung is a potential area for development activities in the marine product processing sector, one of which is salted fish agroindustry. The existence of salted fish agro-industry can serve as a source of income and also create jobs for people on the coast of East Lampung. The study aimed to analyze profit of salted fish agroindustry and to analyze the added value of salted fish agroindustry in Labuhan Maringgai District. The respondents of this study were 4 (four) owners of micro-scale salted fish agro-industry. Qualitative descriptive analysis was used a the method of the analysis in this study by using a case study approach to micro-scale salted fish agro-industry. The results in this study showed that salted fish agroindustry can have a profit of Rp. 1,476,189. Meanwhile, the average added value was Rp. 9,043.98 for japu fish, Rp. 3,589.00 for beaver fish, and Rp. 5,883.01 for anchovies. These results indicated that salted fish agroindustry is profitable and feasible to be developed.